2022
DOI: 10.1097/brs.0000000000004405
|View full text |Cite
|
Sign up to set email alerts
|

Does Post-Operative Spine Infection Bacterial Gram Type Affect Surgical Debridement or Antibiotic Duration?

Abstract: Study Design. This is a retrospective cohort study. Objective. The aim was to evaluate differences in readmission rates, number of debridements, and length of antibiotic therapy when comparing bacterial gram type following lumbar spinal fusion infections. Summary of Background Data. Surgical site infections (SSIs) after spinal fusion serve as a significant source of patient morbidity. It remains to be elucidated how bacterial classification of the infecting organism affects the management of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…They can potentially require multiple revisions, including hardware removal, representing a much higher morbidity burden than the "simpler" route of surgical debridement or antibiotic therapy for less severe SSI. 11,[31][32][33][34][35][36] The current study reports obesity and male sex as significant risk factors for SSI after PSF for AIS. Obesity has been a long-established risk factor for SSI in orthopedic spinal arthrodesis, hypothesized to result from increased inflammatory cell activity and pro-inflammatory cytokines released by adipose tissue, longer operative times, and increased tissue trauma.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…They can potentially require multiple revisions, including hardware removal, representing a much higher morbidity burden than the "simpler" route of surgical debridement or antibiotic therapy for less severe SSI. 11,[31][32][33][34][35][36] The current study reports obesity and male sex as significant risk factors for SSI after PSF for AIS. Obesity has been a long-established risk factor for SSI in orthopedic spinal arthrodesis, hypothesized to result from increased inflammatory cell activity and pro-inflammatory cytokines released by adipose tissue, longer operative times, and increased tissue trauma.…”
Section: Discussionmentioning
confidence: 58%
“…The incidence of SSI is positively associated with both BMI and subcutaneous fat thickness overlying the surgical site. 15,28,35,37 Obesity has further been associated with mixed flora infections in patients undergoing spinal fusion, which have a higher risk of relapse after medical management, requiring prolonged antibiotic courses to clear the SSI if medical management is even successful. 35,36 Furthermore, previous literature has shown that obesity is a paradoxical state of malnutrition, where despite a positive energy balance and potentially significant adiposity, obese patients are frequently severely deficient in crucial micronutrients required for proper wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations